Computational targeting of allosteric site of MEK1 by quinoline‐based molecules - Singh, Rahul; Bhardwaj, Vijay K.; Purohit, Rituraj (Cell biochemistry and function, 2022)
MEK1 is an attractive target due to its role in selective extracellular‐signal‐regulated kinase phosphorylation, which plays a pivotal role in regulating cell proliferation. Another benefit of targeting the MEK protein is its unique hydrophobic pocket that can accommodate highly selective allosteric inhibitors. To date, various MEK1 inhibitors have reached clinical trials against several cancers, but they were discarded due to their severe toxicity and low efficacy. Thus, the development of allosteric inhibitors for MEK1 is the demand of the hour. In this in‐silico study, molecular docking, long‐term molecular dynamics (5 µs), and molecular mechanics Poisson–Boltzmann surface area analysis were undertaken to address the potential of quinolines as allosteric inhibitors. We selected four reference MEK1 inhibitors for the comparative analysis. The drug‐likeness and toxicity of these molecules were also examined based on their ADMET and Toxicity Prediction by Komputer Assisted Technology profiles. The outcome of the analysis revealed that the quinolines (4m, 4o, 4s, and 4n) exhibited better stability and binding affinity while being nontoxic compared to reference inhibitors. We have reached the conclusion that these quinoline molecules could be checked by experimental studies to validate their use as allosteric inhibitors against MEK1. Significance statement Notably, various MEK1 inhibitors were in clinical trial studies to treat pancreatic, colon, breast, and non‐small‐cell lung cancer; however, the trials failed due to severe toxicity and low efficacy. Therefore, validating the need for the development of nontoxic and potential lead candidates as MEK1 inhibitors. In this study, we reported highly potential quinoline scaffolds as MEK1 allosteric inhibitors. Moreover, these molecules have the potential to replace the molecules that possess adverse effects like toxicity and slow biodegradability towards humans.